A study using a graphical syntax for actor‐network theory. Issue 2 (2014) - ,; ,
Abstract : Purpose – Actor‐network theory (ANT) is considered to be both a theoretical position and a methodology. ANT has been the centre of vigorous debates regarding its ontological viewpoint but has also been found to have some drawbacks as a methodology. The purpose of this paper is to use a graphical syntax for ANT to describe the development and implementation of a health information system (IS) in order to assess whether the graphical syntax improves the use of ANT as a methodology.Design/methodology/approach – An extensive example derived from a case study, describing the development and implementation of an electronic patients' records system, is illustrated using this graphical syntax. This serves to makes the actors, translations and black boxes in the case visible.Findings – The syntax is found to help the researcher to conceptualise the research, to highlight assumptions as black boxes and to follow the actor but above all it encourages the researcher to understand the translations being made between actors and to make them explicit. Hence the syntax is found to assist at the analytical phases of a research project. The graphic syntax found to address the criticisms identified for ANT as an IS research methodology.Research limitations/implications – The proposed graphical syntax assists researchers who use ANT as a methodology. Use of the syntax in education is also foreseen to be practical. The evaluation of ANT‐gs in the paper provides an argument for its use but a more reliable argument would be made by collating and analysing feedback from independent modellers who actually use the graphical syntax. This is an important part of future research.Practical implications – The visualisation of the actor‐network provided by ANT‐gs provides a relatively simple representation while at the same time it makes key ANT concepts explicit. This is expected to address the issue of superficial understanding of ANT and selective use of its constructs; it makes the actor‐network boundaries immediately visible. Thus the paper proposes that ANT‐gs will be useful both by IS researchers and as an educational tool but future research is required to verify both these practical implications. The development of a computer‐based modelling tool based on this syntax is proposed to facilitate effective and efficient modelling.Originality/value – This paper proposes a unique tool to support ANT as a methodology. Its use encourages the researcher to focus on constructs that are essential elements of ANT and, by making each of the translation instances explicit, it strengthens the analysis in a way that is true to the view of ANT as a sociology of translation.